Analisis Kemampuan Pemecahan Masalah Berdasarkan Self-Confidence Siswa Pada Materi Bilangan Bulat Kelas VII SMP - Liza Liza; Jamilah jamilah; Dewi Risalah (LPD Universitas PGRI Pontianak, 2026)
Abstract: This study uses a descriptive qualitative method, which aims to analyze student’s self-confidence in mathematical problem solving on integer topics at SMP Kemala Bhayangkari 1 Kubu Raya. The date were collected and described in the from of word, as is characteristic of descriptive research. The study was conducted at SMP Kemala Bhayangkari 1 Kubu Raya. Research data were collected through several techniques, namely tests, questionnaires, and interviews, which were used to analyze students self-confidence in mathematical problem solving. The collected data were then processed into clear and easily understood information. The data sources in this study consisted of six students from class VII B and one mathematics teacher at SMP Kemala Bhayangkari 1 Kubu Raya. The data collection techniques used included measurement techniques, direct communication techniques, and indirect communication techniques, interview guidelines, and documentation. The data analysis techniques used ware data reduction, data presentation, and conclusion drawing. The results of the study indicate that, in general, the higher the students self-confidence, the better their mathematical problem-solving ability. Keywords: Problem-Solving Ability, Integer Topics, Self-Confidence.